Consulting Committee/Contents - BASRASTUDIES JOURNAL, مجلة دراسات البصرة (Basra studies journal, 2025)
The research must specialize in one of the humanitarian studies that is concerned with Basrah Province affairs in particular and Iraqi affairs in general whether in the past, present or future, such as: language, literature, history, geography, sociology, philosophy, libraries and information systems, and other humanitarian studies.